Phosphoinositide 3-Kinase Signaling in Retinal Rod Photoreceptors - Ivanovic, Ivana (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. Phosphoinositide 3-kinase (PI3K) consists of a p110 catalytic protein and a p85α regulatory protein, required for the stabilization and localization of p110-PI3K activity. The biological significance of PI3K was investigated in vertebrate rod photoreceptors by deleting its regulatory p85α protein and examining its role in photoreceptor structure, function, and protein trafficking. METHODS. Mice that expressed Cre recombinase in rods were bred to mice with a floxed p85α (pik3r1) regulatory subunit of PI3K to generate a conditional deletion of pik3r1 in rods. Functional and structural changes were determined by ERG and morphometric analysis, respectively. PI3K activity was measured in retinal homogenates immunoprecipitated with an anti-PY antibody. Akt activation was determined by Western blot analysis with a pAkt antibody. RESULTS. Light-induced stress increased PI3K activity in retinal immunoprecipitates and phosphorylation of Akt. There was no effect of pik3r1 deletion on retinal structure. However, twin flash electroretinography revealed a slight delay in recovery kinetics in pik3r1 knockout (KO) mice compared with wild-type controls. The movement of arrestin in the pik3r1 KO mice was slower than that in the wild-type mouse retinas at 5 minutes of exposure to light. At 10 minutes of exposure, the ROS localization of arrestin was almost identical between the wild-type and pik3r1 KO mice. CONCLUSIONS. The results provide the first direct evidence that rods use PI3K-generated phosphoinositides for photoreceptor function. The lack of phenotype in pik3r1 KO rod photoreceptors suggests a redundant role in controlling PIP(3) synthesis.